Disease Control, Health Resource Use, Healthcare Costs, and Predictors in Gout Patients in the United States, the United Kingdom, Germany, and France: A Retrospective Analysis. Issue 1 (June 2016) - Morlock, Robert; Chevalier, Pierre; Horne, Laura; Nuevo, Javier; Storgard, Chris; Aiyer, Lalitha; Hines, Dionne; Ansolabehere, Xavier; Nyberg, Fredrik
Abstract Introduction The present study aimed to assess disease control, health resource utilization (HRU), and healthcare costs, and their predictors in gout patients across the USA, UK, Germany, and France. Methods Data were extracted from the PharMetrics Plus (USA), Clinical Practice Research Datalink–Hospital Episode Statistics (UK), and Disease Analyzer databases (Germany and France) for adult gout patients over a 3-year period: 2009–2011 (all dates +1 year for France). Patients had "prevalent established gout" (i.e., were treated with urate-lowering therapy [ULT] or eligible for ULT based on American College of Rheumatology guidelines) in the preindex panel-year, with January 1 of the second study year as the study index date. Assessments of disease control (uncontrolled gout definition: ≥1 serum urate (sUA) elevation or ≥2 flares; analysis limited to the subpopulation with sUA) data, HRU, and costs were in the second post-index panel-year, while potential predictors (demographics and gout treatment characteristics) were identified in the first post-index panel-year. Results Treatment rates were high (>70% with chronic urate-lowering treatment in all countries but France), while between 31.3% (France) and 62.9% (USA) of patients remained uncontrolled. Predictors of control included female gender and high adherence. In Germany, the UK, and France, lack of disease control predicted increased gout-attributed costs and increased HRU, both gout-attributed (also in the USA) and non-gout-attributed. Conclusion Gout management remains suboptimal, as many patients remain uncontrolled despite using urate-lowering treatment. Effective and convenient treatment options are needed to improve disease control and minimize additional HRU and costs. Funding AstraZeneca.